ANALISIS PENDAPATAN USAHATANI PADI GOGO DI SINGKUL DESA NGGALAK KECAMATAN REOK BARAT KABUPATEN MANGGARAI - Florensius G. Salmon; I Ketut Arnawa; Utari Vipriyanti; Anglila Amaral (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2022)
The purpose of the study was to determine how much upland rice farming income was in Singkul, Nggalak Village, West Reok District, Manggarai Regency and to determine the efficiency of upland rice farming in Singkul, Nggalak Village, West Reok District, Manggarai Regency. The types of data used are quantitative data and qualitative data, while the sample in this study was 50 people. The results of this study indicate that the average total income (Gross Return) obtained by farmers is Rp. 37,470,000 per person or Rp. 34,376,147 per hectare. The average total production cost (Total Production) spent is Rp. 11,477,700 per person or Rp. 10,530,000 per hectare. The average total income (Net Return) obtained by farmers is Rp. 25,992,300 per person or Rp. 23,846,147 per hectare. Based on the calculation through the R/C formula on upland rice farming in Singkul, Nggalak Village, West Reok District, Manggrai Regency, NTT Province, it was 3.264591. Thus, the R/C value > 1 means that upland rice farming in Singkul, Nggalak Village, West Reok District, Manggrai Regency, NTT Province can be said to be feasible or profitable.